Daya Antibakteri Infusa Daun Asam Jawa (Tamarindus indica Linn) terhadap Streptococcus mutans (Antibacterial Activity of Asam Jawa Leaf Infuse (Tamarindus indica Linn) against Streptococcus mutans - Anggi Faradiba; Achmad Gunadi; Depi Praharani (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Background: Dental caries is a mouth diseases caused by the interaction of host, microorganisms, substrate and time. One of the microorganisms that had played a role in occurrence dental caries is Streptococcus mutans bacteria. Infection caused by S. mutans can be treated with an natural antibacterial or synthetic antibacterial, but synthetic antibacterial has side effects in long term use so we need to do some research to find out natural materials that can be used as an antibacterial to minimize the side effects. Asam jawa leaf (Tamarindus indica L) is one of medicinal plants that have been known contains antibacterial compound namely flavonoid, saponin, alkaloid, vitamin C, chlorine and tanin. Objective: Determined the antibacterial activity of asam jawa leaf infuse against S. mutans. Methods: Laboratories experimental with post test only control group design research. Samples in this research divided into 2 control groups that is negative control (sterile aquadest), positive control (chlorhexidine) and 3 treated groups that is 25%, 50% and 100% asam jawa leaf infuse with 5 total samples for each groups. The antibacterial test was paper disc diffusion method. Antibacterial activity showed by the inhibition zone around the paper disc that indicated there is no bacterial growth. Result and Conclusion: Asam jawa leaf infuse had antibacterial activity against S. mutans and the effective concentration of the asam jawa leaf infuse which had antibacterial activity was 100%. Keywords : Antibacterial, asam jawa leaf infuse, S. mutans.